Changes of temperature during the simple shear test of stainless steel (Archives of Mechanics - Test, 1996)
Investigation of the simple plane shear of stainless steel was carried out. The stress-strain curves and the distributions of infrared radiation for various shear rates have been registered. Temperature changes of the shearing paths were obtained on this ground. It was observed, that this temperature increases both with the increase of the deformation and the rate of shear. The capabilities of the used thermovision system allow us to notice the asymmetry of the thermal distribution of the shear paths caused by the macroscopic shear bands. Finally the results were compared with the results of numerical simulation, obtained for this kind of material deformed in adiabatic conditions.